A coordinated European Union minimum wage policy?. (June 2016) - Fernández-Macías, Enrique; Vacas-Soriano, Carlos
This article contributes to the growing debate on minimum wage coordination at European Union (EU) level. We consider the introduction of a hypothetical EU-wide minimum set at 60 percent of the median wage in each European country; we compare the diverse minimum wage-setting systems across Europe and discuss how they could be affected by such policy. The institutional impact of this European common threshold would be larger in those countries where minimum wages are currently collectively agreed by social partners than in those countries where they are set by statutory regulation. But according to our statistical analysis, such EU-wide minimum wage would affect a larger proportion of the workforce in those countries with statutory minimum wages, since they tend to have a larger low-paid segment of employment.